Processing of silicon-derived silica-bonded silicon carbide membrane supports. Issue 2 (1st February 2019) - Sheng, Hui-Ying; Kim, Young-Wook; Song, In-Hyuck
Abstract: Silicon-derived silica-bonded SiC membrane supports were fabricated by oxidizing the SiC-Si compacts at 1250–1400 °C in air. The effects of initial Si content and sintering temperature on the porosity, pore size, permeability, and mechanical strength of the SiC membrane supports were investigated. The addition of Si into SiC powder compact increased the silica content and flexural strength, but decreased porosity, pore size, and permeability. The strength of silica-bonded SiC membrane supports showed excellent chemical durability (5% and 8% strength degradation after exposure to acidic and alkaline solutions for 63 days, respectively). The excellent chemical durability of silica-bonded SiC membrane supports was attributed to the absence of alkali and alkaline earth elements in its bonding phase. Typical porosity, pore size, permeability, and flexural strength of Si-derived silica-bonded SiC membrane supports (sintered with 30 wt% Si at 1350 °C) are 40%, 1.3 µm, 4.7 × 10 –14 m 2, and 62 MPa, respectively.